Quality of life in women with nausea and vomiting from pregnancy - Mojgan Naeimi rad; Minoor Lamyian (Caspian Journal of Reproductive Medicine, 2015)
Introduction: Nausea and vomiting in early pregnancy is a common complaint, affecting approximately 50-80% of pregnant women. The aim of this study was to determine the effect of the severity of nausea and vomiting from pregnancy on the quality of life during the first trimester of pregnancy.